Exploring the potential of Google Earth as a communication and engagement tool in collaborative Natural Flood Management planning. - Smith, Katherine; Berry, Robert; Clarke, Lucy E. (Geographical Journal, 2020)
This paper considers the development and evaluation of a Google Earth "virtual globe" tour for communicating spatial data and engaging stakeholders in the early stages of a natural flood management (NFM) planning scenario, using a rural UK river catchment that suffered significant flooding in 2007. With a range of diverse stakeholder interests to consider, early engagement and the development of trust before decision-making are essential for the long-term success of such catchment-wide projects. A local catchment group was consulted to identify key information requirements, and from this a "virtual globe" tour was created. The process involved specialist skills and expert leadership, but the end result was accessible to a range of audiences. User evaluation indicated that it was easy to navigate and can be used to stimulate interest and engage stakeholders. Participants trusted the content and valued the interactivity of the tour. It was helpful for communicating and educating participants about the catchment, the issues it faces, and the potential to incorporate NFM, particularly for those with little or no prior knowledge. More abstract information was harder to convey and there were limitations in the availability of suitable data for some variables and the in quality of satellite imagery. This exploratory research found that a Google Earth "virtual globe" tour can be a valuable tool in the initial stages of an NFM project, but there are also opportunities to use this technique in the more advanced stages of the planning process. The approach could be used as part of a wider toolkit for communication and engagement and has potential as a decision support tool in other environmental management scenarios with requirements for public participation, enabling the views of a range of participants to be captured through online distribution and to generate discussion in workshop settings.